Task and ego goal orientations across the youth sports experience - Lochbaum, M.; Kallinen, V.; Konttinen, N. (Studia Sportiva, 2017)
Since the late 1980s, Achievement Goal Theory (AGT) has flourished in the competitive sports research across all age groups. One central proposition is the undifferentiated conception of ability exist until approximately 12 years of age. Given the volume of AGT age-specific studies, quantitative analysis of available youth studies allows for examining whether the goal orientations (i.e., task and ego) scores change based on age (i.e., undifferentiated to the differentiated conception of ability). Hence, the purpose of this quantitative based review was to determine whether task and ego orientation values differ based on age. To achieve our objective, we conducted a meta-analysis with 16 studies meeting specified inclusion criteria one being the use of Perceptions of Success in Sport Questionnaire (POSQ) resulting in 19 samples. The total sample size was 5,679 with 14 studies with mean samples greater than 13-years of age and five equal to or under 12-years of age. The articles came from seven different countries with the USA and Norway accounting exactly half of all represented countries. There was a mix of sports played. Results demonstrated that ego orientation scores did not differ by age category. Initially, task orientation scores appeared to decrease after the age of 12. However, with one outlier removed, a lack of statistical significance (p > .05) resulted. Theoretically, children move in youth to a differentiated conception of ability. It appears even though ability becomes not equal to effort in the minds of youth that self-reported goal orientation values as measured by the POSQ are stable. The implication of such results are many. One being children in competitive sports seemingly have a stable ego orientation score. A critical future research question concerns goal orientation differences among recreational youth sports participation as well as youth who discontinue both competitive and recreational sports participation. The role of goal orientations across these groupings and influence on participation rates is unknown.